Sponge‐induced angiogenesis and inflammation in PAF receptor‐deficient mice (PAFR‐KO) - Ferreira, Mônica A N D; Barcelos, Lucíola S; Campos, Paula P; Vasconcelos, Anilton C; Teixeira, Mauro M; Andrade, Silvia P (British journal of pharmacology, 2004)
To determine biological functions of platelet‐activating factor (PAF) in chronic inflammation, we have investigated the kinetics of angiogenesis, inflammatory cells recruitment and cytokine production in sponge‐induced granuloma in wild type and PAF receptor‐deficient mice (PAFR‐KO). Angiogenesis as determined by morphometric analysis and hemoglobin content was significantly higher in the implants of PAFR‐KO mice at all time points. Treatment with PAF receptor antagonist UK74505 (30 mg kg−1) also increased angiogenesis in sponge implants. Neutrophils and macrophages accumulation, as determined by myeloperoxidase and N‐acetylglucosaminidase activities in the supernatant of implanted sponges were markedly decreased in PAFR‐KO mice. Surprisingly, the levels of the proinflammatory chemokines, keratinocyte‐derived chemokine and chemokine monocyte chemoattractant protein 1 were higher in the implants of the transgenic animals. We have shown that angiogenesis was stimulated in PAFR‐KO mice whereas inflammation was decreased, indicating that PAF is an endogenous regulator of new blood vessels formation in the inflammatory microenvironment induced by the sponge implant. British Journal of Pharmacology (2004) 141, 1185–1192. doi:10.1038/sj.bjp.0705731